2013
DOI: 10.1097/bpo.0b013e31829241dc
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Runners

Abstract: Running biomechanics are significantly altered by shoe type in competitive adolescents. Heavily heeled cushioned trainers promote a heel strike pattern, whereas track flats and barefoot promote a forefoot or midfoot strike pattern. Training in heavily cushioned trainers by the competitive runner has not been clearly shown to be detrimental to performance, but it does change the gait pattern. It is not known whether the altered biomechanics of the heavily heeled cushioned trainer may be detrimental to the adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 13 publications
3
20
1
2
Order By: Relevance
“…Furthermore, our research showed an increase of stride frequency and a decrease of step length when running barefoot. These findings have been reported in many other studies for healthy adult [ 9 ], adolescent [ 5 ] and infantile [ 20 , 31 ] populations. They are probably a consequence of a smaller impact force during landing [ 17 ] but might also be explained by a more cautious gait due to higher proprioception [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, our research showed an increase of stride frequency and a decrease of step length when running barefoot. These findings have been reported in many other studies for healthy adult [ 9 ], adolescent [ 5 ] and infantile [ 20 , 31 ] populations. They are probably a consequence of a smaller impact force during landing [ 17 ] but might also be explained by a more cautious gait due to higher proprioception [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…The last few years, barefoot and barefoot-like running has been widely discussed as a natural alternative to traditional shoe running in recreational sports [ 1 , 2 ]. The long-believed benefits of stable and cushioned running shoes are questioned by findings that show lower prevalence of foot disorders [ 3 , 4 ], improved running economy [ 5 , 6 ] and lower impact forces in barefoot runners [ 5 , 7 , 8 ]. These effects are probably due to alterations in lower extremity running biomechanics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other kinematic differences that have been observed with barefoot running include an increased stride frequency (cadence), a shorter stride length, and less ground contact time. 3 - 6 , 10 , 13 , 20 , 24 , 26 , 38 , 41 Even though the decreased contact time with the ground may influence a reduction in force, the increased cadence may actually have a cumulative effect of joint forces over time. Very limited evidence suggests a decrease in stride length may reduce the probability of a stress fracture by 3% to 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Footwear. Training shoes can significantly alter adolescent runners' biomechanics (Mullen & Toby, 2013), but athletes are often confused by marketing approaches. Running shoes are often sold as a way to either increase comfort or avoid injury, yet there is no valid evidence to justify manufacturers' practice of focusing on pronation control or amount of cushioning (Richards, Magin, & Callister, 2009).…”
Section: Equipmentmentioning
confidence: 99%